2023
DOI: 10.3390/en16010490
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Drivers for Changes in Circular Business Models in a Textile Recycling Sector: Results of Qualitative Empirical Research

Abstract: The growing environmental problems associated with the dumping of large amounts of textile waste and the demand for circular products are prompting textile waste recycling enterprises to develop circular business models (CBMs). This implies a radical change in the way some enterprises operate to obtain growth. Considering the importance of the drivers of and barriers for the adoption and implementation of CBMs in the textile recycling sector, it is claimed that the comprehension of these factors to CBMs is lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Among them, ref. [51], exploring the main enhancing and inhibiting factors for a progress towards circular business models, found that relevant regulations at the European level, appropriate technologies [23,52], and increasing social and environmental awareness of consumers [53][54][55] and managerial capabilities [11,56] are main drivers for changes. However, companies' settings determine their predisposition towards the CE paradigm.…”
Section: Circular Economy: the Transition And The Readiness Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ref. [51], exploring the main enhancing and inhibiting factors for a progress towards circular business models, found that relevant regulations at the European level, appropriate technologies [23,52], and increasing social and environmental awareness of consumers [53][54][55] and managerial capabilities [11,56] are main drivers for changes. However, companies' settings determine their predisposition towards the CE paradigm.…”
Section: Circular Economy: the Transition And The Readiness Levelmentioning
confidence: 99%
“…Ref. [51] explored the textile recycling sector and found that the main enhancing factors are relevant regulations at the European level, appropriate technologies and digitization, and increasing social and environmental awareness of consumers and managerial capabilities. Supply chain complexity was emphasized as one of the main inhibiting factors.…”
Section: Conceptualization Phase: Literature Reviewmentioning
confidence: 99%
“…The complexity of supply chains and collaborations relating to the reuse model were identified as the main barriers [35]. Other barriers to clothing reuse models include consumer disposal practices, producer disposal practices, and recycling technologies, which restrict closing the loop [36].…”
Section: Sellers: Complex Supply Chains For Local Solutionsmentioning
confidence: 99%
“…VTR separates clothing and textile wastes using the most modern, fully computerized lines, able to process 500 tons of materials while assuring sustainability and quality standards, such as ISO 14001 (2015) [53] and ISO 9001 (2015) [54], respectively. Finished products are sorted and packed from 700 different assortment groups, with secondhand clothing sold to over 70 countries and several dozen VIVE Profit stores throughout Poland [35]. The Australian clothing recycling industry can learn from VTR to restrict the disposal to landfills and exporting of EOL clothing.…”
Section: Processes Involved For Secondhand Clothingmentioning
confidence: 99%
“…Regarding the circular economy in terms of manufacturing businesses according to (Balanay et al 2022), other regions such as East and Southeast Asia, Japan, China, Germany, Finland, and the Philippines were also researched in the production, energy, and forestry sectors, where the importance is emphasized and the scientific information is necessary for the advancement of the circular economy for a sustainable sector of profit through innovations that must be brought by the businesses of different countries. Furthermore, regarding the impact of the circular economy on businesses according to (Wójcik-Karpacz et al 2023), the reinforcing factors of sustainable profit in businesses are the right technologies and digitalization, as well as managerial skills. To see the consequences of the circular economy on businesses in developing markets, according to (Dantas et al 2022), the consequences of the circular economy show that policymakers should reevaluate their business policies by promoting open innovation within the circular economy.…”
Section: Introductionmentioning
confidence: 99%